MEDIA SOSIAL RELIGIUS DAN RELIGIUSITAS MAHASISWA: ANALISIS PENGARUH INTENSITAS KONTEN DI UINSI SAMARINDA - Tyas Ayu Ramadhani; M Said Husin; Muhamad Fajri (Jurnal Al-Fatih, 2025)
This study aims to examine the extent to which the intensity of religious content exposure influences the religiosity level of students at Universitas Islam Negeri Sultan Aji Muhammad Idris (UINSI) Samarinda. Employing a quantitative causal-associative approach, the research involved 165 respondents selected from 1,100 active students through simple random sampling. Data were collected using a 5-point Likert scale questionnaire, which was tested for validity using Pearson Product Moment and for reliability using Cronbach’s Alpha (? > 0.80). Analysis was conducted with simple linear regression in SPSS version 29. The findings indicate a significant and positive effect, with an F-test value of 96.047 and a significance level below 0.001, demonstrating that students with higher frequency, longer duration, and stronger emotional engagement with religious content show higher levels of religiosity. These results highlight the potential of social media as a medium for da’wah and Islamic education when properly managed. The study emphasizes the importance of promoting credible, engaging, and interactive religious content, alongside strengthening students’ digital literacy to ensure alignment with authentic Islamic values.